Low-alkalinity matrix composites based on magnesium oxide cement reinforced with cellulose fibres - Mármol de los Dolores, Gonzalo (2017)
A lower-alkalinity cement based on MgO and SiO2 blends is analysed to develop clinker-free Fibre Reinforced Cementitious Composites (FRCC) with cellulosic fibres in order to solve the durability problems of this type of fibres when used in FRCC with Portland cement. Hydration evolution from 7 to 28 days of different MgO-SiO2 formulations is assessed. The main hydration products are Mg(OH)2 and M-S-H gels for all the formulations studied regardless of age. Hardened pastes are obtained with pH values < 11 and good mechanical properties compared to conventional Portland cement. 60% MgO-40% SiO2 system is chosen as optimal for the development FRCC since is the most mechanical resistant and is less alkaline compared with 70% MgO-30% SiO2. FRCC based on magnesium oxide and silica (MgO-SiO2) cement with cellulose fibres are produced to study the durability of lignocellulosic fibres in a lower pH environment than the ordinary Portland cement (PC). Flexural performance and physical tests (apparent porosity, bulk density and water absorption) of samples at 28 days and after 200 accelerated ageing cycles (aac) are compared. Two types of vegetable fibres are utilised: eucalyptus and pine pulps. MgO-SiO2 cement preserves cellulosic fibres integrity after ageing, so composites made out of MgO-SiO2 exhibit significant higher performance after 200 cycles of accelerated ageing than Portland cement composites. High CO2 concentration environment is evaluated as a curing treatment in order to optimise MgO- SiO2 matrices in FRCC. Samples are cured under two different conditions: 1) steam water curing at 55°C and 2) a complementary high CO2 concentration (20% by volume). In carbonated samples, Mg(OH)2 content is clearly lowered while new crystals of hydromagnesite [Mg5 (CO3)4⋅(OH) 2⋅4H2O] are produced. After carbonation, M-S-H gel content is also reduced, suggesting that this phase is also carbonated. Carbonation affects positively to the composite mechanical strength and physical properties with no deleterious effects after ageing since it increases matrix rigidity. The addition of sepiolite in FRCC is studied as a possible additive constituent of the binding matrix. Small cement replacement (1 and 2% wt.) by sepiolite is introduced and studied in hardened cement pastes and, later, in FRCC systems. When used only in cement pastes, it improves Dynamic Modulus of Elasticity over time. Bending tests prove the outcome of this additive on the mechanical performance of the composite: it improves composite homogeneity. Ageing effects are reported after embedding sisal fibres in MgO-SiO2 and PC systems and submitting them to different ageing conditions. This comparative study of fibre degradation applied in different cementitious matrices reveals the real compatibility of lignocellulosic fibres and Mg-based cements. Sisal fibres, even after accelerated ageing, do neither suffer a significant reduction in cellulose content nor in cellulose crystallinity and crystallite size, when exposed to MgO-SiO2 cement. Fibre integrity is preserved and no deposition of cement phases is produced in MgO-SiO2 environment.